Harvest Tech : Air conditioner renewable supply (ACRS) / Muhammad Ainul Imran Mohd Fauzi …[et al.] - Mohd Fauzi, Muhammad Ainul Imran; Mohd Pahlawi, Muhammad Saifuddien; Samsudin, Abd Rahman; Ahmad Nasir, Ahmad Daniel Haikal; Azhari, Muhammad Aflq (2019)
Harvest Tech Company is a company that has do some innovation to the current product. The goal of this company is to generate or supply an electrical energy by harversting the energy from another source that can generate electricity. The concept of our company use is renewable energy and green technology. Air Conditioner Renewable Supply (ACRS) is the first new innovation of our company that has been inspired from the windmill system. This product was an extension od the current product which is air conditioner . ACRS is a product that will attach at the outdoor unit of the air conditioner. This product will harverst the wind energy that has been produce by the outdoor unit of the airconditioner. The electrical energy produced by using the windmill system. This electrical energy will be stored in the battery storage. This energy can be use back by the user or consumer to light up their house or office if and incident occur such as blackout. The target market of our product is for the user of the air conditioner around Shah Alam. This is because the product need an outdoor unit of air conditioner to harvest the wind energy in order to produce the electrical energy. This product is very usefull because it can be as a backup supply when an incident such as blackout occur. This product can help to light up the house when blackout occur. Throughout the concept testing we had done, we found that the existing product does not use the wind energy that have been generated from the outdoor unit of the air conditioner. Beside that, through this concept testing, we also has identify our target market by frequent used of the air conditioner. Moreover, by this additional product that attached to the outdoor unit of the airconditioner, it will help to solve the problem faced y the customer when blackout occur. The market price of the product also affordable for everyone that use the air conditioner and give some advantage to them. The ACRS is a new product that has been innovated by our company. However, there are none of our competitor that combining these two important thing together which give an advantage and add some feature to the product. With this combination of air conditioner system and windmill system its give an advantages to our company to through out the marker. Our company can widely get a huge market because we are combining two product in on price. Our product is a quality product and consist of many features that can solve the user or consumer problem. Our company believe, from this functions and quality product provided from the